A systematic scoping review of medicine availability and affordability in Africa - Jeff Lane; Hilma Nakambale; Asha Kadakia; Yoswa Dambisya; Andy Stergachis; Walter Denis Odoch (BMC Health Services Research, 2024)
Abstract Background The most recent World Medicines Situation Report published in 2011 found substantial medicine availability and affordability challenges across WHO regions, including Africa. Since publication of the 2011 report, medicine availability and affordability has risen on the international agenda and was included in the Sustainable Development Goals as Target 3.8. While numerous medicine availability and affordability studies have been conducted in Africa since the last World Medicines Situation Report, there has not been a systematic analysis of the methods used in these studies, measures of medicine availability and affordability, categories of medicines studied, or geographic distribution. Filling this knowledge gap can help inform future medicine availability and affordability studies, design systems to monitor progress toward Sustainable Development Goal Target 3.8 in Africa and beyond, and inform policy and program decisions to improve medicine availability and affordability. Methods We conducted a systematic scoping review of studies assessing medicine availability or affordability conducted in the WHO Africa region published from 2009–2021. Results Two hundred forty one articles met our eligibility criteria. 88% of the articles (213/241) reported descriptive studies, while 12% (28/241) reported interventional studies. Of the 198 studies measuring medicine availability, the most commonly used measure of medicine availability was whether a medicine was in stock on the date of a survey (124/198, 63%). We also identified multiple other availability methods and measures, including retrospective stock record reviews and self-reported medicine availability surveys. Of the 59 articles that included affordability measures, 32 (54%) compared the price of the medicine to the daily wage of the lowest paid government worker. Other affordability measures were patient self-reported affordability, capacity to pay measures, and comparing medicines prices with a population-level income standard (such as minimum wage, poverty line, or per capita income). The most commonly studied medicines were antiparasitic and anti-bacterial medicines. We did not identify studies in 22 out of 48 (46%) countries in the WHO Africa Region and more than half of the studies identified were conducted in Ethiopia, Kenya, Tanzania, and/or Uganda. Conclusion Our results revealed a wide range of medicine availability and affordability assessment methodologies and measures, including cross-sectional facility surveys, population surveys, and retrospective data analyses. Our review also indicated a need for greater focus on medicines for certain non-communicable diseases, greater geographic diversity of studies, and the need for more intervention studies to identify approaches to improve access to medicines in the region.